Encyclopedia of politics the left and the right - Carlisle, Rodney P. (Gale virtual reference library, 2005)
This two-volume Encyclopedia of Politics: The Left and the Right contains over 450 articles on individuals, movements, political parties, and ideological principles, with those usually thought of as left in the left-hand volume (Volume 1) and those considered on the right, in the right-hand volume (Volume 2).